Antimicrobial titanium/silver PVD coatings on titanium - Ewald, Andrea (BioMed Central, 2006)
BACKGROUND: Biofilm formation and deep infection of endoprostheses is a recurrent complication in implant surgery. Post-operative infections may be overcome by adjusting antimicrobial properties of the implant surface prior to implantation. In this work we described the development of an antimicrobial titanium/silver hard coating via the physical vapor deposition (PVD) process. METHODS: Coatings with a thickness of approximately 2 μm were deposited on titanium surfaces by simultaneous vaporisation of both metals in an inert argon atmosphere with a silver content of approximately 0.7 – 9% as indicated by energy dispersive X-ray analysis. On these surfaces microorganisms and eukaryotic culture cells were grown. RESULTS: The coatings released sufficient silver ions (0.5–2.3 ppb) when immersed in PBS and showed significant antimicrobial potency against Staphylococcus epidermis and Klebsiella pneumoniae strains. At the same time, no cytotoxic effects of the coatings on osteoblast and epithelial cells were found. CONCLUSION: Due to similar mechanical performance when compared to pure titanium, the TiAg coatings should be suitable to provide antimicrobial activity on load-bearing implant surfaces.